Narrative of Nationalism in The Indonesian High School History Textbooks For Grade XI - Guchi, Muslim; Handoko, Satrio Awal (HISTORIKA, 2019)
This study aims to analyze the inculcation of nationalism in Indonesian History textbooks at Class XI High School. The problems raised are: (1) How did the rise of Indonesian nationalism begin? (2) How was revolutionary nationalism in Indonesia? The research method used is content analysis, which is analyzing the content of textbooks on Indonesian history. The approach used is Arnold Joseph Toynbee's theory of "Challenge and Response." The results of the study showed that the rise of nationalism was a "response" to the "challenge" in the form of Dutch colonialism and imperialism. Meanwhile, revolutionary nationalism was a "response" to the emergence of a bright young man who led a new national movement, namely Sukarno, as an educated person who founded a party with the name of the Indonesian National Party. The party is revolutionary, and previously the party was named "Algeemene Studie Club." Sukarno led the party until December 1929. The number of members up to that time reached 1000 people. On October 28, 1928, this organization took part in declaring a pledge about the homeland of one, one nation and one language, namely Indonesia. The Youth Pledge Statement has a broad impact on society to foster strong nationalism.